Reversible supraventricular tachycardia and left bundle branch block in a marathon runner with exertional heat stroke in the Po Valley - Poggiali, Erika; Cervellin, Gianfranco; Valenti, Gioacchino; Barcella, Bruno; Stomeo, Niccolò; Biagi, Andrea; Corvi, Andrea; Vercelli, Andrea; Rossi, Luca (Acta Biomedica Atenei Parmensis, 2023)
We report the case of a 52-year-old marathon runner admitted to our emergency department for exertional heat stroke (EHS). The electrocardiogram (ECG) showed a supraventricular tachycardia, probably an atrial flutter with 2:1 block, conducted with left bundle branch block. After 10 minutes of aggressive fluid management and rapid external cooling, the ECG returned to normal. As the high-sensitivity cardiac troponin I was elevated, coronary angiography and an electrophysiological study were performed, revealing normal coronary arteries and excluding inducible arrhythmias. As reported in the current literature, our findings confirm that the electrocardiographic changes and elevation of cardiac markers in EHS do not reflect cardiac ischemia, but rather a myocardial injury due to the pathophysiological response to dehydration and hyperthermia, which markedly impaired stroke volume and cardiac output. EHS is a life-threatening condition with a complex pathophysiology caused by thermoregulatory failure. Diagnosis is not always straightforward, but early recognition and timely management (the “golden hour”) with rapid cooling and intravenous fluids are crucial to prevent irreversible and fatal organ damage. EHS is defined by a rectal temperature > 40.5 °C with symptoms or signs of neurological dysfunction, such as confusion, drowsiness, or seizures, which can rapidly worsen with delirium, coma, and cardiac arrest. With this case report, we want to remind emergency physicians that early diagnosis and appropriate management of EHS can avoid death and inappropriate treatment. (www.actabiomedica.it)